Resting-state functional connectivity alterations in post-stroke cognitive impairment: a systematic review - Sagues, Elena; Alfaro, Francisco; Ramos-Rodríguez, Ramón; García-Casares, Natalia (Springer Nature, 2025)
Post-stroke cognitive impairment is a common and highly disabling multi-domain cognitive decline with unclear pathophysiological mechanisms. Its extent may be predicted by functional neuroimaging techniques, which could enhance our understanding of its underlying pathophysiology. Synthesize the state-of-the-art knowledge on resting-state functional magnetic resonance imaging findings in post-stroke cognitive impairment, their correlation with cognitive performance and the secondary compensatory connectivity changes. We performed a qualitative systematic literature review of reported data of resting-state functional magnetic resonance imaging abnormalities in post-stroke cognitive impairment, consulting the electronic databases Medline, Scopus, Web of Science, Cochrane, and BASE until June 2024. We selected 23 studies. They reported several key brain areas and network abnormalities associated with post-stroke cognitive impairment compared to controls and non-demented patients. The main areas with decreased functional connectivity were the medial prefrontal cortex, the inferior frontal gyrus, the posterior and anterior cingulate cortex, the precuneus and the hippocampus. The principal network altered was the default mode network, which includes the majority of the brain structures previously mentioned. Additionally, increased functional connectivity in other contralesionally areas may represent maladaptive or compensatory changes post-stroke. Resting-state functional magnetic resonance imaging is a promising tool for studying functional changes associated with post-stroke cognitive impairment. It may enhance our understanding of its pathophysiology and improve selection of suitable period or candidates for cognitive rehabilitation.
Keywords: Cerebro - Enfermedades - Complicaciones y secuelas; Redes neuronales (Neurobiología); Functional magnetic resonance; Functional connectivity; Resting-state; Post-stroke cognitive impairment; Networks